Advances in the research of nano delivery systems in ischemic stroke - Li, Yi-Xuan; Wang, Hong-Bo; Jin, Jian-Bo; Yang, Chun-Lin; Hu, Jing-Bo; Li, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Ischemic stroke is the most common type of cerebrovascular disease with high disability rate and mortality. The blood-brain barrier (BBB) protects the homeostasis of the brain's microenvironment and impedes the penetration of 98% of drugs. Therefore, effective treatment requires the better drug transport across membranes and increased drug distribution. Nanoparticles are a good choice for drugs to cross BBB. The main pathways of nano delivery systems through BBB include passive diffusion, adsorption-mediated endocytosis, receptor-mediated transport, carrier-mediated transport, etc. At present, the materials used in brain-targeted delivery can be divided into natural polymer, synthetic polymers, inorganic materials and phospholipid. In this review, we first introduced several ways of nano delivery systems crossing the BBB, and then summarized their applications in ischemic stroke. Based on their potential and challenges in the treatment of ischemic stroke, new ideas and prospects are proposed for designing feasible and effective nano delivery systems.